Cone survival and preservation of visual acuity in an animal model of retinal degeneration. Issue 11 (2nd April 2013) - Piano, Ilaria; Novelli, Elena; Gasco, Paolo; Ghidoni, Riccardo; Strettoi, Enrica; Gargini, Claudia
Abstract The prevention of cone loss during retinal degeneration is a major goal of most therapeutic strategies in retinal degenerative diseases. An intriguing issue in the current research in this field is to understand why a genetic mutation that affects rods eventually leads to cone death. The main objective of the present study was to investigate to what extent rescuing rods from degeneration affects the survival of cones and prevents functional impairment of the visual performance. To this purpose, we compared rod and cone viabilities by both ex vivo and in vivo determinations in the rd10 mutant mouse, a validated model of human retinitis pigmentosa. The ex vivo experiments included morphological and biochemical tests, whereas in vivo studies compared the rod‐mediated scotopic with the cone‐mediated photopic electroretinogram. We also determined the overall visual performance by behaviorally testing the visual acuity (VA). The electroretinogram measurements showed that the kinetics of the photopic response in rd10 mice was slowed down with respect to the age‐paired wild‐type at a very early stage of the disease, when rods were still present and responsive. We then tested cone viability and function under a pharmacological scheme previously shown to prolong rod survival. The treatment consisted of eye drop administration of myriocin, an inhibitor of the biosynthesis of ceramide, a powerful proapoptotic messenger. The results of biochemical, morphological and functional assays converged to show that, in treated rd10 mice cone photoreceptors, the inner retina and overall visual performance were preserved well after rod death.